Nilai Sosial dan Budaya dalam Novel Guru Aini Karya Andrea Hirata - Sumarni Sumarni; Sudirman Shomary (UIR Press, 2023)
Sociology of literature is a research that examines the relationship of literary works with humans in society and their social processes. The novel Guru Aini by Andrea Hirata contains many elements of sociology of literature, especially social and cultural values. The problems in this study are (1) what are the social values ​​contained in the novel Guru Aini by Andrea Hirata?, (2) what are the cultural values ​​in the novel Guru Aini by Andrea Hirata?. The purpose of this study is to describe, analyze, and conclude the social and cultural values ​​contained in the novel Guru Aini by Andrea Hirata. The theory used in this study is the theory of Sikana (1986), Zubaedi (2009), Koentjaraningrat (2009) and other theories that support this research. The data source is the entire contents of the novel Guru Aini by Andrea Hirata. The approach used in this research is a qualitative approach with the type of library research. The method used is descriptive method. The data collection technique used is hermeneutic technique. The results of the research on social and cultural values ​​in the novel Guru Aini by Andrea Hirata contained 22 data, consisting of social values, namely (1) loves (affection) there were 9 data such as help, dedication, kinship, loyalty, and caring, (2 ) responsibility (responsibility) there is 1 data such as a sense of empathy, (3) life harmony (harmony of life) there are 2 data such as cooperation and discipline. Cultural values ​​contained in the novel Guru Aini by Andrea Hirata, namely language there are 2 data such as expressions and greeting words, living equipment systems and technology there are 2 data such as means of transportation, livelihood systems there are 4 data such as traders, drivers and fishermen, religious systems There are 2 data such as praying and belief.